Synthesis, Characterization, and Catalytic Studies of Mn(III)-Schiff Base-Dicyanamide Complexes: Checking the Rhombicity Effect in Peroxidase Studies - Manuel R. Bermejo; Rocío Carballido; M. Isabel Fernández-García; Ana M. González-Noya; Gustavo González-Riopedre; Marcelino Maneiro; Laura Rodríguez-Silva (Journal of Chemistry)
The condensation of 3-methoxy-2-hydroxybenzaldehyde and the diamines 1,2-diphenylendiamine, 1,2-diamine-2-methylpropane and 1,3-propanediamine yielded the dianionic tetradentate Schiff base ligands N,N′-bis(2-hydroxy-4-methoxybenzylidene)-1,2-diphenylendiimine (H2L1), N,N′-bis(2-hydroxy-4-methoxybenzylidene)-1,2-diamino-2-methylpropane (H2L2) and N,N′-bis(2-hydroxy-4-methoxybenzylidene)-1,3-diaminopropane (H2L3) respectively. The organic compounds H2L1 and H2L2 have been characterized by elemental analysis, IR, 1H and 13C NMR spectroscopies and mass spectrometry electrospray (ES). The crystal structure of H2L2 in solid state, solved by X-ray crystallography, is highly conditioned in the solid state by two N-H•••N intramolecular interactions. The synthesis of three new manganese(III) complexes 1–3, incorporating these ligands, H2L1–H2L3, and dicyanamide (DCA), is reported. The complexes 1–3 have been physicochemically characterized by elemental analysis, IR and paramagnetic 1H NMR spectroscopy, ESI mass spectrometry, magnetic moment at room temperature and conductivity measurements. Complex 1 has been crystallographically characterized. The X-ray structure shows the self-assembly of the Mn(III)-Schiff base-DCA complex through µ-aquo bridges between neighbouring axial water molecules and also by π-π stacking interactions, establishing a dimeric structure. The manganese complexes were also tested as peroxidase mimics for the H2O2-mediated reaction with the water-soluble trap ABTS, showing complexes 1-2 relevant peroxidase activity in contrast with 3. The rhombicity around the metal ion can explain this catalytic behaviour.